Giving Birth in Canada, 1900-1950 - Mitchinson, Wendy (Book collections on Project MUSE., 2002)
"In Giving Birth in Canada, the first historical study of childbirth in Canada, Wendy Mitchinson has written a fascinating account of childbirth rituals in the first half of the twentieth century. Thorough and comprehensive, the work is based on a rich variety of sources, including medical textbooks, the medical periodical press, popular medical advice books, literature published in women's magazines, patient records, and interviews with women who gave birth and physicians who practised during the period." "While the book focuses on conventional medical practices, the author's survey of midwifery and Aboriginal birthing practices provides a counterpoint to the approach taken by Western medicine and permits valuable discussion about the dynamics of gender and race as they relate to childbirth and, more broadly, to early-twentieth-century Canada."--Jacket